Candida arteritis occurring in a liver transplant recipient. Issue 3 (21st April 2014) - Lladó, L.; Solé, C.; Bodro, M.; Baliellas, C.; Sabé, N.; Petit, A.; Ramos, E.; Carratalà, J.; Fabregat, J.
Abstract We report the first case, to our knowledge, of Candida arteritis in a liver transplant recipient. The patient presented with hemorrhagic shock requiring emergency arterial repair. As Candida albicans, Candida tropicalis, and Candida glabrata were growing in the arterial tissue, the patient received antifungal therapy for 5 months, but died because of chronic graft dysfunction. No evidence of fungal infection was found in the tissue on postmortem examination.